Forsterite-based high-temperature heat storage material and preparation method thereof

By combining modified carbonized rice husk powder and forsterite and other materials, forsterite is prepared with high thermal conductivity, photothermal conversion efficiency, compressive strength and cycle stability, which solves the problems of low thermal conductivity, low photothermal conversion efficiency, low pressure strength and poor cycle stability in the prior art.

CN119591395AActive Publication Date: 2025-03-11WUHAN UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411546640.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Existing high-temperature heat storage materials have problems such as low thermal conductivity, low photothermal conversion efficiency, low pressure resistance and poor circulation stability.

Method used

By immersing the carbonized rice husk powder in a silica sol and heat treatment, a modified carbonized rice husk powder is formed, and then mixed with forsterite powder, boron carbide micro powder, vanadium pentoxide micro powder, manganese nanoferrate powder and other materials, and after pressing and high-temperature heat treatment, a forsterite-based high-temperature heat storage material is prepared.

Benefits of technology

The prepared forsterilite-based high-temperature heat storage material has high thermal conductivity, high photothermal conversion, high pressure resistance and good cycle stability. It is suitable for the temperature range of 800 to 1400℃.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a forsterite-based high-temperature heat storage material and a preparation method thereof. According to the technical scheme, the preparation method comprises the following steps: impregnating carbonized rice husk powder in silica sol, performing pressure impregnation, and drying to obtain modified carbonized rice husk powder; uniformly mixing the modified carbonized rice husk powder, boron carbide micro powder and vanadium pentoxide micro powder, and performing heat treatment to obtain a mixture A; uniformly mixing forsterite powder, the mixture A, silica powder, magnesium oxide micro powder, a polyvinyl alcohol solution and nano manganese ferrite powder to obtain a mixture B; and carrying out compression molding on the mixture B, carrying out heat treatment at 800-900 DEG C for 1-2 hours under the argon or nitrogen atmosphere condition, and then carrying out heat treatment at 1100-1300 DEG C for 2-4 hours to obtain the forsterite-based high-temperature heat storage material. The forsterite-based high-temperature heat storage material prepared by the method is high in heat conductivity, high in photo-thermal conversion efficiency, high in compression strength and good in cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of refractory materials, and specifically relates to a forsterite-based high-temperature heat storage material and a preparation method thereof. Background Art

[0002] With the rapid development of economic globalization and the continuous growth of population, the demand and supply of energy continue to increase. However, the non-renewable characteristics of traditional fossil energy such as coal, oil, and natural gas, as well as environmental pollution problems, make the development of sustainable renewable energy a top priority. Although solar energy resources are abundant, their utilization is restricted by factors such as geography, seasons, day and night, and weather changes, and exhibits characteristics such as intermittent and instability. Sensible heat storage technology utilizes the high specific heat of solid thermal storage materials to store and release thermal energy through the changes in thermal energy during the process of increasing and decreasing the temperature of the material itself. The selection of solid thermal storage materials mainly considers photothermal conversion efficiency, heat storage capacity, thermal conductivity, high temperature stability, thermal shock stability, etc. The technicians in this field have conducted in-depth research on this:

[0003] The patented technology of "A forsterite-based solar thermal storage ceramic and its preparation method and application (CN202310513313.6)". The forsterite-based thermal storage material prepared by this technology has the advantages of high strength and high thermal storage density, but has the problems of low thermal conductivity and low photothermal conversion capacity.

[0004] The patented technology of "A silicon carbide-based ceramic thermal storage body and its preparation method (CN202310513313.6)" generates forsterite in situ on the surface of silicon carbide. The prepared composite ceramic thermal storage body has high specific heat and good thermal conductivity, but the radiation-absorption capacity of the material is low, which limits its application in the field of solar thermal storage.

[0005] The patented technology of "A new type of high-efficiency composite thermal storage body and its preparation method (CN202111214375.4)" physically encapsulates the phase change medium in large-sized pores of silicon carbide to prepare a sensible heat-specific heat composite thermal storage body. Although the thermal storage capacity of the composite material is improved, the composite material has problems such as low thermal conductivity and poor cycle stability.

[0006] The patented technology "A method for preparing a honeycomb ceramic thermal storage material (CN201710775785.3)" mainly uses bauxite and kyanite as the main raw materials and adopts an extrusion molding preparation method to prepare a honeycomb ceramic thermal storage body. Although the thermal storage body has a large heat exchange area and high heat storage efficiency, it has low compressive strength and low photothermal conversion efficiency.

[0007] In summary, existing high-temperature thermal storage materials have the following technical defects: low thermal conductivity, low photothermal conversion efficiency, low compressive strength and poor cycle stability. Summary of the invention

[0008] The present invention aims to overcome the technical defects of the prior art and has the objective of providing a method for preparing a forsterite-based high-temperature thermal storage material. The forsterite-based high-temperature thermal storage material prepared by the method has high thermal conductivity, high photothermal conversion rate, high compressive strength and good cycle stability.

[0009] To achieve the above purpose, the specific steps of the technical solution adopted by the present invention are:

[0010] Step 1: immerse the carbonized rice husk powder in silica sol at a temperature of 160-180° C. and a pressure of 1.1-1.7 MPa for 40-60 min, and then dry at 100-110° C. for 10-12 h to obtain modified carbonized rice husk powder.

[0011] Step 2: Evenly mix 95-97 wt % of the modified carbonized rice husk powder, 1-2 wt % of boron carbide powder and 2-3 wt % of vanadium pentoxide powder, and heat treat the mixture at 600-700° C. for 2-4 h to obtain a mixture A.

[0012] Step 3, 50-70wt% of forsterite powder, 10-20wt% of mixture A, 5-10wt% of silicon powder, 5-10wt% of magnesium oxide powder, 5-7wt% of 5% polyvinyl alcohol solution and 3-5wt% of nano manganese ferrite powder are mixed uniformly to obtain mixture B.

[0013] Step 4: Press the mixed material B into shape at 80-100 MPa, heat treat the green body at 800-900° C. for 1-2 h in an argon or nitrogen atmosphere, and then heat treat it at 1100-1300° C. for 2-4 h to obtain a forsterite-based high-temperature thermal storage material.

[0014] The particle size of the carbonized rice husk powder is less than 0.088 mm; the chemical composition of the carbonized rice husk powder is: C is 20-40wt%, SiO2 is 20-40wt%, and the ignition loss is 50-60wt%.

[0015] The average particle size of the silica sol is 8-25 nm; the chemical composition of the silica sol is: the content of SiO2 is greater than 25.50 wt%, the content of Na2O is less than 0.35 wt%; the pH of the silica sol is 8.5-9.5.

[0016] The particle size of the boron carbide powder is 2-4 μm; the B4C content of the boron carbide powder is greater than 99.9 wt%.

[0017] The particle size of the vanadium pentoxide fine powder is 2-4 μm; the V2O5 content of the vanadium pentoxide fine powder is greater than 99 wt%.

[0018] The particle size of the forsterite powder is less than 0.088 mm; the chemical composition of the forsterite powder is as follows: the content of SiO2 is greater than 45wt%, the content of MgO is greater than 45wt%, the content of Fe2O3 is less than 8wt%, and the content of other impurities is less than 0.2wt%.

[0019] The particle size of the silicon micropowder is less than 35 μm; the SiO2 content of the silicon micropowder is greater than 95.0 wt%.

[0020] The particle size of the magnesium oxide powder is 1-10 μm; the MgO content of the magnesium oxide is greater than 99.9 wt%.

[0021] The particle size of the nano manganese ferrite powder is 60-100 nm; the MnFe2O4 content of the nano manganese ferrite powder is greater than 99wt%.

[0022] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:

[0023] (1) The present invention utilizes the physical and chemical change characteristics of boron carbide micropowder and vanadium pentoxide micropowder such as melting and oxidation under heat treatment conditions to obtain modified carbonized rice husk powder coated with silicon dioxide; the modified carbonized rice husk powder is fully reacted to form silicon carbide whiskers in situ inside the powder during the heat treatment process, thereby forming a thermal conductive network inside the composite material, making full use of the high thermal conductivity of the silicon carbide whiskers, so that the prepared forsterite-based high-temperature thermal storage material has high thermal conductivity.

[0024] (2) The present invention combines the high solar absorption rate of manganese ferrite and the high thermal conductivity of silicon carbide. By adding nano manganese ferrite powder during the preparation process, combined with the high specific heat capacity of forsterite and in-situ synthesized silicon carbide whiskers, the material is endowed with high solar absorption, heat conduction and heat storage capabilities. Therefore, the prepared forsterite-based high-temperature thermal storage material has a high light-to-heat conversion efficiency.

[0025] (3) The present invention makes full use of the magnesium oxide powder and the silicon dioxide on the surface of the modified carbonized rice husk powder to form forsterite in situ during the heat treatment process, thereby improving the antioxidant performance. Combined with the excellent high temperature stability and chemical stability of forsterite, the prepared forsterite-based high temperature thermal storage material has good cycle stability; at the same time, fine-crystalline forsterite is formed by the reaction of magnesium oxide powder and silicon powder between forsterite powder particles, which promotes the sintering and densification of forsterite-based high temperature thermal storage materials. Therefore, the prepared forsterite-based high temperature thermal storage material has high compressive strength and excellent cycle stability.

[0026] The use temperature range of the forsterite-based high-temperature thermal storage material prepared by the present invention is 800-1400°C; the main properties of the forsterite-based high-temperature thermal storage material are tested: the volume density is ≥2.86g / cm 3; Thermal conductivity ≥50W / (m·K); The average absorptivity in the solar light band (200-2000nm) is above 90%, and the photothermal conversion efficiency reaches 80-86%; The compressive strength is 80-100MPa; The thermal shock stability is ≥20 times (1100℃, air cooling); No new phase is generated after 100 thermal cycles, and the mass change rate is ≤0.5wt% (800-1400℃).

[0027] Therefore, the forsterite-based high-temperature thermal storage material prepared by the present invention has high thermal conductivity, high photothermal conversion efficiency, high compressive strength and good cycle stability. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific implementation methods, which does not limit the scope of protection thereof.

[0029] A forsterite-based high-temperature heat storage material and a preparation method thereof. The preparation method described in this specific embodiment is:

[0030] Step 1: immerse the carbonized rice husk powder in silica sol at a temperature of 160-180° C. and a pressure of 1.1-1.7 MPa for 40-60 min, and then dry at 100-110° C. for 10-12 h to obtain modified carbonized rice husk powder.

[0031] Step 2: Evenly mix 95-97 wt % of the modified carbonized rice husk powder, 1-2 wt % of boron carbide powder and 2-3 wt % of vanadium pentoxide powder, and heat treat the mixture at 600-700° C. for 2-4 h to obtain a mixture A.

[0032] Step 3, 50-70wt% of forsterite powder, 10-20wt% of mixture A, 5-10wt% of silicon powder, 5-10wt% of magnesium oxide powder, 5-7wt% of 5% polyvinyl alcohol solution and 3-5wt% of nano manganese ferrite powder are mixed uniformly to obtain mixture B.

[0033] Step 4: Press the mixed material B into shape at 80-100 MPa, heat treat the green body at 800-900° C. for 1-2 h in an argon or nitrogen atmosphere, and then heat treat it at 1100-1300° C. for 2-4 h to obtain a forsterite-based high-temperature thermal storage material.

[0034] The chemical composition of the carbonized rice husk powder is: C is 20-40wt%, SiO2 is 20-40wt%, and the ignition loss is 50-60wt%.

[0035] The chemical components of the silica sol are: the content of SiO2 is greater than 25.50wt%, the content of Na2O is less than 0.35wt%; the pH of the silica sol is 8.5-9.5.

[0036] The chemical composition of the forsterite powder is as follows: the content of SiO2 is greater than 45wt%, the content of MgO is greater than 45wt%, the content of Fe2O3 is less than 8wt%, and the content of other impurities is less than 0.2wt%.

[0037] The SiO2 content of the silicon micropowder is greater than 95.0wt%.

[0038] In this specific implementation mode:

[0039] The particle size of the carbonized rice husk powder is less than 0.088 mm;

[0040] The average particle size of the silica sol is 8 to 25 nm;

[0041] The particle size of the boron carbide powder is 2 to 4 μm, and the B4C content of the boron carbide powder is greater than 99.9 wt%;

[0042] The particle size of the vanadium pentoxide micropowder is 2 to 4 μm, and the V2O5 content of the vanadium pentoxide micropowder is greater than 99 wt%;

[0043] The particle size of the forsterite powder is less than 0.088 mm;

[0044] The particle size of the silicon powder is less than 35 μm;

[0045] The particle size of the magnesium oxide powder is 1 to 10 μm, and the MgO content of the magnesium oxide is greater than 99.9 wt %;

[0046] The particle size of the nano manganese ferrite powder is 60-100 nm; the MnFe2O4 content of the nano manganese ferrite powder is greater than 99wt%.

[0047] This will not be described in detail in the embodiments.

[0048] Example 1

[0049] A forsterite-based high-temperature heat storage material and a preparation method thereof. The preparation method described in this embodiment is:

[0050] Step 1: Immerse the carbonized rice husk powder in silica sol at a temperature of 160° C. and a pressure of 1.1 MPa for 40 minutes, and then dry at 100° C. for 10 hours to obtain modified carbonized rice husk powder.

[0051] Step 2: 95 wt% of the modified carbonized rice husk powder, 2 wt% of boron carbide powder and 3 wt% of vanadium pentoxide powder are mixed evenly, and heat treated at 600° C. for 2 h to obtain a mixture A.

[0052] Step 3: Evenly mix 50 wt% of forsterite powder, 20 wt% of the mixture A, 10 wt% of silicon powder, 10 wt% of magnesium oxide powder, 7 wt% of a 5% polyvinyl alcohol solution and 3 wt% of nano manganese ferrite powder to obtain a mixture B.

[0053] Step 4: Press the mixed material B into a shape at 80 MPa, heat treat the green body at 800° C. for 1 h in an argon atmosphere, and then heat treat the green body at 1100° C. for 2 h to obtain a forsterite-based high-temperature thermal storage material.

[0054] The chemical composition of the carbonized rice husk powder is: C is 20.2wt%, SiO2 is 40wt%, and the ignition loss is 50.8wt%.

[0055] The chemical composition of the silica sol is: the content of SiO2 is 25.60wt%, the content of Na2O is 0.34wt%; the pH of the silica sol is 9.5.

[0056] The chemical composition of the forsterite powder is as follows: SiO2 content is 45.2wt%, MgO content is 50wt%, Fe2O3 content is 7.9wt%, and the content of other impurities is 0.18wt%.

[0057] The SiO2 content of the silicon micropowder is 97wt%.

[0058] The forsterite-based high-temperature thermal storage material prepared in this embodiment has an operating temperature range of 800-1400°C. The main properties are tested as follows: the volume density is 2.86 g / cm 3 ; Thermal conductivity is 61.85W / (m·K); The average absorptivity in the solar light band (200-2000nm) is 90.8%, and its photothermal conversion efficiency is 85.6%; The compressive strength is 83.2MPa; The thermal shock stability is 25 times (1100℃, air cooling); No new phase is generated after 100 thermal cycles, and the mass change rate is 0.48wt% (800-1400℃).

[0059] Example 2

[0060] A forsterite-based high-temperature heat storage material and a preparation method thereof. The preparation method described in this embodiment is:

[0061] Step 1: Immerse the carbonized rice husk powder in silica sol at a temperature of 170° C. and a pressure of 1.3 MPa for 50 minutes, and then dry at 105° C. for 11 hours to obtain modified carbonized rice husk powder.

[0062] Step 2: 96 wt% of the modified carbonized rice husk powder, 2 wt% of boron carbide powder and 2 wt% of vanadium pentoxide powder are mixed evenly, and heat treated at 650° C. for 3 h to obtain a mixture A.

[0063] Step 3: Evenly mix 58 wt% of forsterite powder, 16 wt% of mixture A, 8 wt% of silicon powder, 8 wt% of magnesium oxide powder, 6 wt% of 5% polyvinyl alcohol solution and 4 wt% of nano manganese ferrite powder to obtain mixture B.

[0064] Step 4: Press the mixed material B into shape at 90 MPa, heat treat the green body at 850° C. for 1.5 h in an argon atmosphere, and then heat treat it at 1200° C. for 3 h to obtain a forsterite-based high-temperature thermal storage material.

[0065] The chemical composition of the carbonized rice husk powder is: C is 30.8wt%, SiO2 is 31wt%, and the ignition loss is 55.5wt%.

[0066] The chemical composition of the silica sol is: the content of SiO2 is 27wt%, the content of Na2O is 0.31wt%; the pH of the silica sol is 9.2.

[0067] The chemical composition of the forsterite powder is as follows: SiO2 content is 47wt%, MgO content is 48wt%, Fe2O3 content is 7wt%, and the content of other impurities is 0.16wt%.

[0068] The SiO2 content of the silicon micropowder is 98wt%.

[0069] The forsterite-based high-temperature thermal storage material prepared in this embodiment has an operating temperature range of 800-1400°C. The main properties have been tested: the volume density is 2.95 g / cm 3 The thermal conductivity is 57.34W / (m·K). The average absorptivity in the solar wavelength range (200-2000nm) is 92.6%, and the photothermal conversion efficiency is 84.3%. The compressive strength is 86.5MPa. The thermal shock stability is 23 times (1100℃, air cooling). No new phase is generated after 100 thermal cycles, and the mass change rate is 0.46wt% (800-1400℃).

[0070] Example 3

[0071] A forsterite-based high-temperature heat storage material and a preparation method thereof. The preparation method described in this embodiment is:

[0072] Step 1: Immerse the carbonized rice husk powder in silica sol at a temperature of 170° C. and a pressure of 1.5 MPa for 50 minutes, and then dry at 105° C. for 11 hours to obtain modified carbonized rice husk powder.

[0073] Step 2: 96 wt% of the modified carbonized rice husk powder, 2 wt% of boron carbide powder and 2 wt% of vanadium pentoxide powder are mixed evenly, and heat treated at 650° C. for 3 h to obtain a mixture A.

[0074] Step 3: Evenly mix 64 wt% of forsterite powder, 13 wt% of mixture A, 6 wt% of silicon powder, 7 wt% of magnesium oxide powder, 6 wt% of 5% polyvinyl alcohol solution and 4 wt% of nano manganese ferrite powder to obtain mixture B.

[0075] Step 4: Press the mixed material B into shape at 90 MPa, heat treat the green body at 850° C. for 1.5 h in a nitrogen atmosphere, and then heat treat it at 1200° C. for 3 h to obtain a forsterite-based high-temperature thermal storage material.

[0076] The chemical composition of the carbonized rice husk powder is: C is 33.6wt%, SiO2 is 26wt%, and the ignition loss is 57.9wt%.

[0077] The chemical composition of the silica sol is: the content of SiO2 is 28.5wt%, the content of Na2O is 0.3wt%; the pH of the silica sol is 8.8.

[0078] The chemical composition of the forsterite powder is as follows: SiO2 content is 48wt%, MgO content is 46wt%, Fe2O3 content is 6.5wt%, and the content of other impurities is 0.17wt%.

[0079] The SiO2 content of the silicon micropowder is 98wt%.

[0080] The forsterite-based high-temperature thermal storage material prepared in this embodiment has an operating temperature range of 800-1400°C. The main properties are tested as follows: the volume density is 2.93 g / cm 3 ; Thermal conductivity is 52.56W / (m·K); The average absorptivity in the solar light band (200-2000nm) is 92.9%, and its photothermal conversion efficiency is 83.6%; The compressive strength is 91.7MPa; The thermal shock stability is 22 times (1100℃, air cooling); No new phase is generated after 100 thermal cycles, and the mass change rate is 0.45wt% (800-1400℃).

[0081] Example 4

[0082] A forsterite-based high-temperature heat storage material and a preparation method thereof. The preparation method described in this embodiment is:

[0083] Step 1: Immerse the carbonized rice husk powder in silica sol at a temperature of 180° C. and a pressure of 1.7 MPa for 60 minutes, and then dry at 110° C. for 12 hours to obtain modified carbonized rice husk powder.

[0084] Step 2: 97 wt % of the modified carbonized rice husk powder, 1 wt % of boron carbide powder and 2 wt % of vanadium pentoxide powder are mixed evenly, and heat treated at 700° C. for 4 h to obtain a mixture A.

[0085] Step 3: Evenly mix 70 wt% of forsterite powder, 10 wt% of mixture A, 5 wt% of silicon powder, 5 wt% of magnesium oxide powder, 5 wt% of 5% polyvinyl alcohol solution and 5 wt% of nano manganese ferrite powder to obtain mixture B.

[0086] Step 4: Press the mixed material B into shape at 100 MPa, heat treat the green body at 900° C. for 2 h in a nitrogen atmosphere, and then heat treat the green body at 1300° C. for 4 h to obtain a forsterite-based high-temperature thermal storage material.

[0087] The chemical composition of the carbonized rice husk powder is: C is 40wt%, SiO2 is 20wt%, and the ignition loss is 60wt%.

[0088] The chemical composition of the silica sol is: the content of SiO2 is 30wt%, the content of Na2O is 0.28wt%; the pH of the silica sol is 8.5.

[0089] The chemical composition of the forsterite powder is as follows: SiO2 content is 50wt%, MgO content is 45wt%, Fe2O3 content is 6wt%, and the content of other impurities is 0.18wt%.

[0090] The SiO2 content of the silicon micropowder is 96wt%.

[0091] The forsterite-based high-temperature thermal storage material prepared in this embodiment has an operating temperature range of 800-1400°C. The main properties are tested as follows: the volume density is 3.02 g / cm 3The thermal conductivity is 50.13W / (m·K). The average absorptivity in the solar light band (200-2000nm) is 94.3%, and the photothermal conversion efficiency is 80.9%. The compressive strength is 98.8MPa. The thermal shock stability is 20 times (1100℃, air cooling). No new phase is generated after 100 thermal cycles, and the mass change rate is 0.41wt% (800-1400℃).

[0092] Compared with the prior art, this specific implementation has the following positive effects:

[0093] (1) This specific embodiment utilizes the physical and chemical change characteristics of boron carbide micropowder and vanadium pentoxide micropowder such as melting and oxidation under heat treatment conditions to obtain modified carbonized rice husk powder coated with silicon dioxide; the modified carbonized rice husk powder is fully reacted to form silicon carbide whiskers in situ inside the powder during the heat treatment process, thereby forming a thermal conductive network inside the composite material, making full use of the high thermal conductivity of the silicon carbide whiskers, so that the prepared forsterite-based high-temperature thermal storage material has high thermal conductivity.

[0094] (2) This specific embodiment combines the high solar absorption rate of manganese ferrite and the high thermal conductivity of silicon carbide. By adding nano manganese ferrite powder during the preparation process, combined with the high specific heat capacity of forsterite and in-situ synthesized silicon carbide whiskers, the material is endowed with high solar absorption, heat conduction and heat storage capabilities. Therefore, the prepared forsterite-based high-temperature thermal storage material has a high light-to-heat conversion efficiency.

[0095] (3) This specific implementation method makes full use of the magnesium oxide micropowder and the silicon dioxide on the surface of the modified carbonized rice husk powder to form forsterite in situ during the heat treatment process, thereby improving the antioxidant performance. Combined with the excellent high temperature stability and chemical stability of forsterite, the prepared forsterite-based high temperature thermal storage material has good cycle stability; at the same time, fine-crystalline forsterite is formed by the reaction of magnesium oxide micropowder and silicon micropowder between forsterite powder particles, which promotes the sintering and densification of forsterite-based high temperature thermal storage materials. Therefore, the prepared forsterite-based high temperature thermal storage material has high compressive strength and excellent cycle stability.

[0096] The use temperature range of the forsterite-based high-temperature thermal storage material prepared in this specific embodiment is 800-1400°C; the main properties of the forsterite-based high-temperature thermal storage material have been tested: volume density ≥ 2.86g / cm 3 ; Thermal conductivity ≥50W / (m·K); The average absorptivity in the solar light band (200-2000nm) is above 90%, and the photothermal conversion efficiency reaches 80-86%; The compressive strength is 80-100MPa; The thermal shock stability is ≥20 times (1100℃, air cooling); No new phase is generated after 100 thermal cycles, and the mass change rate is ≤0.5wt% (800-1400℃).

[0097] Therefore, the forsterite-based high-temperature thermal storage material prepared in this specific embodiment has high thermal conductivity, high photothermal conversion efficiency, high compressive strength and good cycle stability.

Claims

1. A method for preparing a forsterite-based high-temperature thermal storage material, characterized in that The steps of the preparation method are: Step 1, immersing the carbonized rice husk powder in silica sol at a temperature of 160-180° C. and a pressure of 1.1-1.7 MPa for 40-60 min, and then drying at 100-110° C. for 10-12 h to obtain modified carbonized rice husk powder; Step 2, 95-97 wt% of the modified carbonized rice husk powder, 1-2 wt% of boron carbide powder and 2-3 wt% of vanadium pentoxide powder are uniformly mixed, and heat treated at 600-700° C. for 2-4 hours to obtain a mixture A; Step 3, 50-70wt% of forsterite powder, 10-20wt% of mixed material A, 5-10wt% of silicon powder, 5-10wt% of magnesium oxide powder, 5-7wt% of 5% polyvinyl alcohol solution and 3-5wt% of nano manganese ferrite powder are uniformly mixed to obtain mixed material B; Step 4: Press the mixed material B into shape at 80-100 MPa, heat treat the green body at 800-900° C. for 1-2 h in an argon or nitrogen atmosphere, and then heat treat it at 1100-1300° C. for 2-4 h to obtain a forsterite-based high-temperature thermal storage material.

2. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the carbonized rice husk powder is less than 0.088 mm; the chemical composition of the carbonized rice husk powder is: C is 20-40wt%, SiO2 is 20-40wt%, and the ignition loss is 50-60wt%.

3. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The average particle size of the silica sol is 8-25 nm; the chemical composition of the silica sol is: the content of SiO2 is greater than 25.50 wt%, the content of Na2O is less than 0.35 wt%; the pH of the silica sol is 8.5-9.

5.

4. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the boron carbide powder is 2-4 μm; the B4C content of the boron carbide powder is greater than 99.9 wt%.

5. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the vanadium pentoxide fine powder is 2-4 μm; the V2O5 content of the vanadium pentoxide fine powder is greater than 99 wt%.

6. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the forsterite powder is less than 0.088 mm; the chemical composition of the forsterite powder is as follows: the content of SiO2 is greater than 45wt%, the content of MgO is greater than 45wt%, the content of Fe2O3 is less than 8wt%, and the content of other impurities is less than 0.2wt%.

7. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the silicon micropowder is less than 35 μm; the SiO2 content of the silicon micropowder is greater than 95.0 wt%.

8. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the magnesium oxide powder is 1-10 μm; the MgO content of the magnesium oxide is greater than 99.9 wt%.

9. The method for preparing the forsterite-based high-temperature thermal storage material according to claim 1, characterized in that: The particle size of the nano manganese ferrite powder is 60-100 nm; the MnFe2O4 content of the nano manganese ferrite powder is greater than 99wt%.

10. A forsterite-based high-temperature heat storage material, characterized in that The forsterite-based high-temperature thermal storage material is a forsterite-based high-temperature thermal storage material prepared according to the method for preparing a forsterite-based high-temperature thermal storage material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of honeycomb ceramic heat storage material

    CN107459335A

  • Novel efficient composite heat accumulator and preparation method thereof

    CN114184073A

  • Silicon carbide-based ceramic heat accumulator and preparation method thereof

    CN116730731A

  • Forsterite light aggregate and preparation method of same

    CN103396105A

  • Nano-aperture porous periclase-forsterite ceramic material and preparation method thereof

    CN107445594A